2017
DOI: 10.1002/sat.1233
|View full text |Cite
|
Sign up to set email alerts
|

Smart gateways switching control algorithms based on tropospheric propagation forecasts

Abstract: Summary The use Q/V band spectrum for the feeder links of high throughput satellites and the need to cope with the significant propagation impairments at those frequencies motivate the development of smart diversity techniques. Those techniques aim at improving the availability level of the overall feeder link with a limited level of redundancy. The combinatorial gain of availability provided by those techniques can be obtained only if efficient switching methodologies are developed, performing the best trade‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Applications of the NWP-based propagation impairments simulator to FMTs are proposed by for earth observation data downlink using ACMs, by Jeannin et al ( , 2019 for smart gateways switching and for site diversity. Tentative for predicting the scintillation using NWP models has also been proposed by Pereira et al (2014) and Marziani et al (2019).…”
Section: 1029/2022rs007553mentioning
confidence: 99%
“…Applications of the NWP-based propagation impairments simulator to FMTs are proposed by for earth observation data downlink using ACMs, by Jeannin et al ( , 2019 for smart gateways switching and for site diversity. Tentative for predicting the scintillation using NWP models has also been proposed by Pereira et al (2014) and Marziani et al (2019).…”
Section: 1029/2022rs007553mentioning
confidence: 99%
“…First, we select all members of the PEARP forecasts archived in 2014 and 2015 around the receiving station of interest. In some cases the weather forecast is realistic, but even a slight phase error may lead to the double-penalty problem (Nurmi, 2003). Therefore, we consider here a 100 × 100 km box around the attenuation observation site such as that in Theis et al (2005).…”
Section: The Attenuation Statistical Prediction Modelmentioning
confidence: 99%
“…In this respect, the use of meteorological forecasts constitutes a promising approach to control the decision process associated with those fade compensation mechanisms. This has, for instance, been studied in Paraboni et al (2009), Biscarini et al (2016) and Jeannin et al (2017) for different applications. One of the major difficulties highlighted by those studies is that the attenuation induced by rain on Earth-space links is not strongly correlated to the model outputs due to the model accuracy and its limited space and time resolutions.…”
Section: Introductionmentioning
confidence: 99%
“…Notably good statistical agreements were reported at 20.2 GHz in the south of France for small scale diversity sites over a one-year period [11]. Other studies have shown promises for the applications of NWP forecasts directly to FMTs [12], [13], or similarly for space missions [14], [15]. A more thorough statistical validation of the NWP performances would however still benefit any design based on them.…”
Section: Introductionmentioning
confidence: 96%